The value of radiation therapy in the treatment of W ilms tumor - Leborgne, F; Leborgne, J H (Cirugía del Uruguay, 1972)
A retrospective analysis is presented on 51 cases of Wilms' tumor seen 1953 through 1969. No survivors were seen in a group of 12 cases with inoperable or me.tastatic tumors treated with incomplete surgical resection or radiotherapy only. Nine out of 20 cases (54 % ) survived after nephrectomy and postoperative irradiation, whilst 11 out of 14 cases ( 79 % ) survived after preoperative irradiation, nephrectomy and in sone cases postoperative irradiation. Survival in resectable cases under the age of 2 years was 78 %, and 41 % for cases over the age of 2 years. Out of 14 cases treated with the association of Actinomycin D 64 % survived, whereas 71 % survive_d in a comparable group of 14 cases where the drug was omited. Pulmonary prophylactic irradiation seems to have improved the cure rate: out of 11 cases so treated 82 % survived, whilst out of 17 cases whose lungs were not irradiated prophylactically, 59 % survived.